APLIKASI COMMODITY SYSTEM ASSESSMENT METHOD (CSAM) DALAM DISTRIBUSI CABAI ( Capsicum annum L) DARI PETANI DI KECAMATAN PENEBEL SAMPAI PENGECER - Kresnawan, I Gusti Ngurah Cahyadi; Hartiati, Amna; Sedana Yoga, I Wy Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 6 No 4 (2018): DesemberDO - 10.24843/JRMA.2018.v06.i04.p13, 2018)
The purpose of this study were (1) to determine the number of chili ( Capsicum annum L) distribution lines from farmers in Penebel Subdistrict to the retailers, (2) find out the type of chili postharvest handling from farmers in Penebel District to retailers and find out the impact of losses from farmers in the District Penebel to retailers. The method used in this study is a survey method with the application of a questionnaire Commodity System Assessment Method that is distributed to farmers, collectors, traders, and retailers. The results of the study show that there are 3 distribution channels, namely lane I - retailers, lane II farmers - collectors - retailers, lane III farmers - collectors - traders - retailers. Handling at the farm level includes harvesting, cleaning and sorting, packaging, postharvest handling at the level of collectors, traders and retailers including weighing, cleaning and sorting, packaging and transportation. The impact of the loss of chili postharvest at the farmer level is significant at 10.48%, at the level of collectors in the sorting process is insignificant reaching 2.80%, at the level of large traders in the sorting process is insignificant reaching 2.2% and at the retail level at the sorting process is significant reaching 6.41%. Keywords : Chili, CSAM and Distribution channel